Kecemasan dan Pola Makan (Studi Pada Tikus)
<span data-sheets-value=""1":2,"2":"The authors were keen to explore the dynamics of stress or anxiety towards the eating behavior of rats. Female non-obese rats (Rattus norvegicus, N=10)), weighing each between 180-220 mg and aged 3-4 mo were divided into a control and an experimental group. After 3 days of “domestication time” to get the baseline data, the experimental group were exposed to a hungry cat outside their cages in the experimental room, during 3 consecutive days and nights. A camera was used to help continuous observation. Data were analysed with the Wilcoxon and U-Man Whitney statistical technique. Results reveal that anxiety affects the eating pattern of the experimental group, though only on day 1. "" data-sheets-userformat=""2":15357,"3":"1":0,"5":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"6":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"7":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"8":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"10":0,"11":3,"12":0,"14":"1":2,"2":0,"15":"Calibri","16":11">The authors were keen to explore the dynamics of stress or anxiety towards the eating behavior of rats. Female non-obese rats (Rattus norvegicus, N=10)), weighing each between 180-220 mg and aged 3-4 mo were divided into a control and an experimental group. After 3 days of “domestication time” to get the baseline data, the experimental group were exposed to a hungry cat outside their cages in the experimental room, during 3 consecutive days and nights. A camera was used to help continuous observation. Data were analysed with the Wilcoxon and U-Man Whitney statistical technique. Results reveal that anxiety affects the eating pattern of the experimental group, though only on day 1. <span data-sheets-value=""1":2,"2":"The authors were keen to explore the dynamics of stress or anxiety towards the eating behavior of rats. Female non-obese rats (Rattus norvegicus, N=10)), weighing each between 180-220 mg and aged 3-4 mo were divided into a control and an experimental group. After 3 days of “domestication time” to get the baseline data, the experimental group were exposed to a hungry cat outside their cages in the experimental room, during 3 consecutive days and nights. A camera was used to help continuous observation. Data were analysed with the Wilcoxon and U-Man Whitney statistical technique. Results reveal that anxiety affects the eating pattern of the experimental group, though only on day 1. "" data-sheets-userformat=""2":15357,"3":"1":0,"5":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"6":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"7":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"8":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"10":0,"11":3,"12":0,"14":"1":2,"2":0,"15":"Calibri","16":11">Peneliti tertarik untuk mengetahui dinamika stres atau kecemasan terhadap pola makan tikus betina (Rattus norvegicus). Subjek tikus betina yang tak kegemukan (N=10) yang berbobot seputar 180-220 mg dan berumur 3-4 bulan, dibagi menjadi 2 kelompok, kelompok kontrol dan kelompok eksperimen Setelah di-“jinakkan” untuk memperoleh data awal, kelompok eksperimen dalam kandang di tengah ruang percobaan, dipajankan terhadap seekor kucing yang telah dibuat lapar, selama 3 hari dan malam berturut-turut. Observasi bersinambung dibantu dengan kamera perekam. Data dianalisis dengan teknik statistik Wilcoxon dan U Mann-Whitney. Hasil menunjukkan adanya pengaruh kecemasan terhadap pola makan kelompok eksperimen, sekalipun hanya pada hari pertama. , number=1, journal=ANIMA Indonesian Psychological Journal, author=Santoso, Agus and Pramadi, Andrian, year=2006, month=Oct., pages=74-85